"We are a transit station here": The role of Israeli oncology social workers in responding to mental health distress and suicidality in patients with cancer. (16th March 2021) - Granek, Leeat; Nakash, Ora; Shapira, Shahar; Ariad, Samuel; Ben-David, Merav A.
ABSTRACT: Social workers have a prominent role in responding to cancer patients' mental health needs. Given the risk of mental health distress in cancer patients, and given that social workers are responsible for responding to these needs, the purpose of this study was to explore how social workers describe their role in responding to mental health distress and suicidality in people with cancer. The Grounded Theory method of data collection and analysis was used. Eighteen social workers were recruited and interviewed. Social workers saw themselves and acted as an interprofessional hub for their patients. This approach was based on the values of holistic care, multiple treatment modalities, interpersonal consultation, and continuity of care. From this standpoint, social workers offered their patients (and at times, their families) comprehensive services providing emotional, behavioral and practical support within the hospital setting, but also outside of it in the patient's communities. Consideration should be paid to promote systemic changes to acknowledge and compensate oncology socials workers' invisible labor that includes both emotional carryover and continuous engagement in their role as liaison and intermediaries for their patients.